A theoretical model for coal swelling induced by gas adsorption in the full pressure range - Ping Guo (Adsorption Science & Technology)
The phenomenon of coal swelling caused by gas adsorption is well known. For Enhanced Coal Bed Methane Recovery and carbon storage, coal swelling induced by gases adsorption may cause significant reservoir permeability change. In this paper, based on the assumption that the surface energy change caused by adsorption is equal to the change in elastic energy of the coal matrix, a theoretical model is derived to describe coal swelling induced by gas adsorption in the full pressure range. The Langmuir constant, coal density, solid elastic modulus, and Poisson’s ratio are required in this model. These model parameters are easily obtained through laboratory testing. The developed model is verified by available experimental data. The results show that the presented model shows good agreement with the experimental observations of swelling. The model errors are within 14% for pure gas, and within 20% for mixed gas. It is shown that this model is able to describe coal swelling phenomena for full pressure range and different gas type including pure gas and mixed. In addition, it is also shown that the errors of the presented model and the Pan’s model are almost the same, but the presented model is solved more easily.